Multivariate Sobel–Uppuluri–Galambos-type bounds - Seneta, E.; John T. Chen (Український математичний журнал, 2000)
We improve the known upper and lower bounds for the probability of the fact that exactly k ievents should occur in a group consisting of n ievents simultaneously for all i= 1, 2, ..., d. Уточнюються відомі верхні та нижні оцінки для ймовірностей того, що відбудеться рівно ki подій в групі з ni подій одночасно при всіх i= 1, 2, ..., d.